2016
DOI: 10.1039/c6cp05904j
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of triarylmethyl radicals with DNA termini revealed by orientation-selective W-band double electron–electron resonance spectroscopy

Abstract: Spin labels selectively attached to biomolecules allow high-accuracy nanoscale distance measurements using pulsed Electron Paramagnetic Resonance (EPR), in many cases providing the only access to structure of complex biosystems. Triarylmethyl (TAM) radicals have recently emerged as a new type of spin labels expanding the applicability of the method to physiological temperatures. Along with other factors, the accuracy of the obtained distances crucially relies on the understanding of interactions between biomol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Pulsed EPR studies with TAMs confirm most of the expected advantages for EPR tomography, oximetry, and precise distance measurements of up to 5 nm in DNAs and in proteins . TAM labels gave a noticeably narrower distribution of distances than typical nitroxides in nucleic acids and a beneficial increase in sensitivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulsed EPR studies with TAMs confirm most of the expected advantages for EPR tomography, oximetry, and precise distance measurements of up to 5 nm in DNAs and in proteins . TAM labels gave a noticeably narrower distribution of distances than typical nitroxides in nucleic acids and a beneficial increase in sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Against this promising background, an inherent weakness of spin labels containing the FTAM core has emerged. FTAM is quite lipophilic and can participate in self‐aggregation, noncovalent binding to lipophilic regions of proteins or membranes, and noncovalent docking to DNA termini . This poorly controlled, spontaneous behavior can produce spin dephasing and enhances spin relaxation as reported in some EPR experiments .…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer‐range distance measurements using pulsed ESR methods provide useful insight into the conformation and dynamics of DNA and RNA as well as on protein–DNA interactions . For such experiments, nitroxide‐based spin labels have been incorporated into both single stranded and duplex DNA and RNA by attachment to specific nucleotides, sugar–phosphate backbone, or termini . In many cases, the flexibility of the spin label can complicate the interpretation of distances in terms of DNA/RNA structure.…”
Section: Figurementioning
confidence: 99%
“…Triarylmethyl (TAM or trityl)-based spin labels represent a potent alternative to nitroxides for EPR distance measurements in biomolecules (51–53). Recently, we reported that double spin-labeling using TAMs allows obtaining narrower spin–spin distance distributions in DNA duplexes and provides higher accuracy of measurement as compared to nitroxide labels (54, 55). Moreover, we have proven that these EPR data are in good agreement with NMR and MD simulation results (56).…”
Section: Introductionmentioning
confidence: 99%